Umowa czy harmonia społeczna - Korab-Karpowicz, W. Julian (Societas et Ius, 2017)
There are some well-known critiques of social contract undertaken from the traditionalist, communitarian and Marxist perspectives. This article suggests a different, rationalist approach: the return to classical rationality. I show that the idea of the social contract has its basis in the mistaken modern assertions concerning human nature, identifying human beings as individuals moved by desires and the will to power, and the phenomenon of life as an endless conflict. I argue that cooperation is essential to human life. It is cooperation and the presence of ethics in the public and private spheres that makes us fully human and civilized beings. The community organized according to the requirements of cooperation is a truly happy and harmonious society.